2019
DOI: 10.3390/plants8110496
|View full text |Cite
|
Sign up to set email alerts
|

Highly Predictive Genetic Markers Distinguish Drug-Type from Fiber-Type Cannabis sativa L

Abstract: Genetic markers can be used in seeds and in plants to distinguish drug-type from fiber-type Cannabis Sativa L. varieties even at early stages, including pre-germination when cannabinoids are not accumulated yet. With this aim, this paper reports sequencing results for tetrahydrocannabinolic acid synthase (THCAS) and cannabidiolic acid synthase (CBDAS) genes from 21 C. sativa L. varieties. Taking into account that THCAS- and CBDAS-derived enzymes compete for the same substrate, the novelty of this work relies i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(60 citation statements)
references
References 38 publications
7
53
0
Order By: Relevance
“…In particular, the authors hypothesized that the B T and B D alleles could be part of a wider allelic series coding for several isoenzymatic forms of THCA- and CBDA-synthase, respectively, with differential affinities for the CBGA substrate, resulting in significantly different CBD/THC ratios observed in the heterozygotes. Further studies pointed out the existence of several allelic variants of B D [ 7 , 20 , 24 ] and B T [ 7 , 8 , 24 , 25 ] genes coding for less or totally non-functional CBDA- and THCA-synthase, respectively, and which therefore, influence the cannabinoid profile of the plant and, from a practical point of view, also represent an useful genetic marker to differentiate the drug-type from the fibre-type C. sativa L. plants. Interestingly, a higher number of allelic variants of wild-type B D locus was found in comparison to the B T locus.…”
Section: Biochemistry Genetic Taxonomy and Legal Status Of mentioning
confidence: 99%
“…In particular, the authors hypothesized that the B T and B D alleles could be part of a wider allelic series coding for several isoenzymatic forms of THCA- and CBDA-synthase, respectively, with differential affinities for the CBGA substrate, resulting in significantly different CBD/THC ratios observed in the heterozygotes. Further studies pointed out the existence of several allelic variants of B D [ 7 , 20 , 24 ] and B T [ 7 , 8 , 24 , 25 ] genes coding for less or totally non-functional CBDA- and THCA-synthase, respectively, and which therefore, influence the cannabinoid profile of the plant and, from a practical point of view, also represent an useful genetic marker to differentiate the drug-type from the fibre-type C. sativa L. plants. Interestingly, a higher number of allelic variants of wild-type B D locus was found in comparison to the B T locus.…”
Section: Biochemistry Genetic Taxonomy and Legal Status Of mentioning
confidence: 99%
“…Another missense mutation was described from a cultivar from Turkey that is considered a weak BDw variant resulting in a partial accumulation of CBGA due to partly impaired activity of the encoded CBDAS (Onofri et al 2015). In THCA-dominant cultivars, fragments have been found that are 93% identical to functional CBDAS and share a four base pair deletion that results in a truncated and most probably nonfunctional protein (Weiblen et al 2015;Cascini et al 2019;Vergara et al 2019). This deletion showed strict association with THCA-producing cultivars, suggesting tight genetic linkage with THCAS.…”
Section: Cannabinoid Oxidocyclase Gene Evolutionmentioning
confidence: 99%
“…This deletion showed strict association with THCA-producing cultivars, suggesting tight genetic linkage with THCAS. Indeed, it could be used to discriminate between fiber and drug-type cultivars as well as accurately predict chemotype in feral and cultivated plants (Cascini et al 2019;Wenger et al 2020). Notably, up to three different variants of such putative pseudogenes were detected in single cultivars (van Bakel et al 2011;Weiblen et al 2015;Laverty et al 2019;Vergara et al 2019) suggesting multiple duplicated loci.…”
Section: Cannabinoid Oxidocyclase Gene Evolutionmentioning
confidence: 99%
“…Recently, others have proposed targeted markers for the identification of fiber and resin cannabis (e.g. Cascini et al 2019;Hilyard et al 2019) as well as molecular sexing tools to differentiate feminized from regular seed stock (Toth et al 2020).…”
Section: Introductionmentioning
confidence: 99%